TRAFFIC MANAGEMENT AND ENGINEERING WORKS FOR HALIM LRT-HSR INTEGRATION STATION IN JAKARTA-CIKAMPEK TOLL ROAD SEGMENT Km.1+280 TO 1+420 - pamuji, rachmat; Widyatami , Filki Suri (Jurnal Teknik Sipil, 2022)
The study of traffic engineering management is very different, causing the condition to exist. Traffic Engineering Management (MRLL) can make macroscopic in the pre-feasibility study stage, with concern to guide its macro transportation system, may also include its own details (microscopic). Traffic impact control policies are also included, be it road management efforts, priority management and demand management. As the main project, the project is related to the public road which will giving influence is the interference of over-the-counter so the contractor or the owner of the work must make a real contribution in the distribution of transactions through all that happens. This study was designed using literature and field research conducted and analyzed measurably. In this research, the introduction of the study area is a very important part of preparation in order to better understand the characteristics of the location. The expected results in this study are to analyze the impact that occurs in each condition of the work carried out and provide recommendations for handling the impacts obtained in each of these conditions.